Improving Literacy Through Technology: An Agile Approach in the Development of the Redify Digital Reading Platform - Muhammad Fikri Aqil; Rosidah; Muh Galang Nusantara; Siti Fatimah Azzahra Namar; Rafiqah Ameliah Kasim; Elma Nurjannah (Journal of Embedded Systems, Security and Intelligent Systems, 2024)
In the digital age, reading has evolved from a traditional physical book to a more dynamic and technology-integrated activity through e-books and other digital platforms. However, this progress also presents new challenges, such as a significant decline in reading interest in Indonesia, especially among the younger generation. Redify, an innovation in the digital reading ecosystem, addresses this challenge by offering a more engaging reading experience and incorporating a strong community approach. This article explores how Redify leverages the latest technologies and agile development methods to quickly adapt its features to meet readers' needs and preferences. By encouraging social interaction and discussion among readers, Redify aims to revive reading habits and improve the overall reading experience. The study also assesses the feasibility and effectiveness of Redify's strategy in overcoming the decline in reading interest among the younger generation in Indonesia.